2019
DOI: 10.1002/ajpa.23839
|View full text |Cite
|
Sign up to set email alerts
|

Variations in epiphyseal fusion and persistence of the epiphyseal line in the appendicular skeleton of two identified modern (19th–20th c.) adult Portuguese and Italian samples

Abstract: Objectives: The aim of this work is to study age, sex, and population variations in epiphyseal fusion and persistence of the epiphyseal line in the appendicular skeleton of two identified modern (19th-20th c.) adult skeletal samples, using a specifically designed macroscopic scoring method. The use of epiphyseal closure and persistence of the epiphyseal line as an adult-age marker is also discussed. Materials and methods: This study examined 981 adult skeletons of both sexes from two identified modern (20th c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…This is consistent with the findings of Monge Calleja and co‐workers (Monge Calleja et al, 2020), as with the application of the method in a larger sample (61 individuals) the metric features showed a reduced accuracy. Genetic, environmental and sociocultural factors (such as malnutrition, diseases, and lifestyle) may play a very important role in establishing sex‐related differences among populations (Hall, 1978; Johnston & Zimmer, 1989; Scheuer and McLaughlin‐Black, Scheuer & Maclaughin‐Black, 1994; Belcastro et al, 2019). Actually, differences between Italian and Portuguese populations already emerged in previous studies focused on other postcranial skeletal features in adult samples (e.g., sacral vertebral body fusion, variations in epiphyseal fusion) (Belcastro et al, 2019; Belcastro, Rastelli, & Mariotti, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of Monge Calleja and co‐workers (Monge Calleja et al, 2020), as with the application of the method in a larger sample (61 individuals) the metric features showed a reduced accuracy. Genetic, environmental and sociocultural factors (such as malnutrition, diseases, and lifestyle) may play a very important role in establishing sex‐related differences among populations (Hall, 1978; Johnston & Zimmer, 1989; Scheuer and McLaughlin‐Black, Scheuer & Maclaughin‐Black, 1994; Belcastro et al, 2019). Actually, differences between Italian and Portuguese populations already emerged in previous studies focused on other postcranial skeletal features in adult samples (e.g., sacral vertebral body fusion, variations in epiphyseal fusion) (Belcastro et al, 2019; Belcastro, Rastelli, & Mariotti, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, environmental and sociocultural factors (such as malnutrition, diseases, and lifestyle) may play a very important role in establishing sex‐related differences among populations (Hall, 1978; Johnston & Zimmer, 1989; Scheuer and McLaughlin‐Black, Scheuer & Maclaughin‐Black, 1994; Belcastro et al, 2019). Actually, differences between Italian and Portuguese populations already emerged in previous studies focused on other postcranial skeletal features in adult samples (e.g., sacral vertebral body fusion, variations in epiphyseal fusion) (Belcastro et al, 2019; Belcastro, Rastelli, & Mariotti, 2008). Several studies observed inter‐population variation in the degree of sexual dimorphism of various pelvic features (Patriquin, Loth, & Sten, 2003; Steyn, Pretorius, & Hutten, 2004; Walker, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Active periosteal reaction noted on the inner side of one rib body usually indicates the presence of some lower respiratory tract disease (Davies Barret et al 2019), while the presence of the same reaction on the right femur could be due to trauma, metabolic disease, or some other factor (Ortner 2003; Waldron 2009). The presence of epiphyseal lines on the right femur and humerus in this middle-aged adult indicate this may have occurred as a consequence of disturbances in growth and development, malnutrition (Johnston, Zimmer 1989), environmental and sociocultural factors (Johnston, Zimmer 1989;Belcastro et al 2019), or perhaps due to some kind of hard physical labour Anthropological analyses showed that the most of individuals buried at this site had poor health status, visible through presence of CO, PH, and periostitis (see SM 3). Although in all cases lesions were healed, they are however indicative of hard childhood and nutritional imbalance of these individuals.…”
Section: Highway E-70 521kmmentioning
confidence: 86%
“…These collections have been the subject of a large body of research focused on various topics. The latter include methodological studies focused on estimation of age-at-death and attribution of sex [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], the study of entheseal changes in modern humans [62][63][64][65][66][67], and the discussion of their variability among extinct taxa [1][2][3][4]. Additional topics of investigation have been the various expression and demographic distribution of skeletal morphological variants and pathological changes [68][69][70][71], as well as dental and palate traits [72][73][74][75][76].…”
Section: Scientific Osteological Collections and Their Utilitymentioning
confidence: 99%
“…Similarly, anthropological methods of forensic relevance are continuously being developed and implemented on the DHOC of the University of Bologna. Age estimation methods built upon biological data of the osteological collections encompass a technique based on the observations of the timing of fusion of secondary ossification centers of the postcranium [47,48,51,54,55], morphological aspects of the os coxae [52,53], and dental features such as the pulp/tooth ratio among canine teeth [49,50] for adults, while diaphyseal linear growth was documented for the leg in subadults [61]. Sex attribution methods were developed with the aid of three-dimensional morphometrics considering the adult morphology of the human cranium and ankle [56,57,80,81,84].…”
Section: Forensic Purposes In the Use Of Human Osteological Collectionsmentioning
confidence: 99%